2018
DOI: 10.1109/tsg.2016.2634124
|View full text |Cite
|
Sign up to set email alerts
|

Undetectable Timing-Attack on Linear State-Estimation by Using Rank-1 Approximation

Abstract: Abstract-Smart-grid applications based on synchrophasor measurements have recently been shown to be vulnerable to timing attacks. A fundamental question is whether timing attacks could remain undetected by bad-data detection algorithms used in conjunction with state-of-the-art situational-awareness state estimators.In this paper, we analyze the detectability of timing attacks on linear state-estimation. We show that it is possible to forge delay attacks that are undetectable. We give a closed form for an undet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…It is shown that a time-variable FDI is able to evade detection via existing detection methods [21]- [22]. Reference [23] considered the cyber-attacks on GPSsynchronized measurements, which gives the attackers the ability of creating time-variable FDIs simply by shifting the measurements in time. Time-varying FDI parameters were also considered in [13]- [14], where it is argued that once the attackers have accessed the system to impose constant FDIs, they can also impose time-variable FDIs with the same efforts and equipment.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…It is shown that a time-variable FDI is able to evade detection via existing detection methods [21]- [22]. Reference [23] considered the cyber-attacks on GPSsynchronized measurements, which gives the attackers the ability of creating time-variable FDIs simply by shifting the measurements in time. Time-varying FDI parameters were also considered in [13]- [14], where it is argued that once the attackers have accessed the system to impose constant FDIs, they can also impose time-variable FDIs with the same efforts and equipment.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…We now introduce the system model that is the same as in [8], [9], we present the attack model and we define rank-1 UTSAs.…”
Section: System and Attack Modelsmentioning
confidence: 99%
“…These are physical attacks that are neither prevented nor detected by the cryptographic tools used by the synchronization protocol. As a result, the phase of phasor measurements is shifted, which can non-negligibly impact the state estimation of the system, as it was shown in [8], [9].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations